Chiral Phosphoric Acid Catalyzed Asymmetric Ugi Reaction by Dynamic Kinetic Resolution of the Primary Multicomponent Adduct. (21st March 2016) - Zhang, Yun; Ao, Yu‐Fei; Huang, Zhi‐Tang; Wang, De‐Xian; Wang, Mei‐Xiang; Zhu, Jieping
Abstract: Reaction of isonitriles with 3‐(arylamino)isobenzofuran‐1(3 H )‐ones in the presence of a catalytic amount of an octahydro ( R )‐binol‐derived chiral phosphoric acid afforded 3‐oxo‐2‐arylisoindoline‐1‐carboxamides in high yields with good to high enantioselectivities. An enantioselective Ugi four‐center three‐component reaction of 2‐formylbenzoic acids, anilines, and isonitriles was subsequently developed for the synthesis of the same heterocycle. Mechanistic studies indicate that the enantioselectivity results from the dynamic kinetic resolution of the primary Ugi adduct, rather than from the C−C bond‐forming process. The resulting heterocycle products are of significant medicinal importance.